2008
DOI: 10.1523/jneurosci.1819-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic D1and D2Receptors Are Essential for the Arousal Effect of Modafinil

Abstract: Modafinil is a wake-promoting compound with low abuse potential used in the treatment of narcolepsy. Although the compound is reported to affect multiple neurotransmitter systems such as catecholamines, serotonin, glutamate, GABA, orexin, and histamine, however, the molecular mechanism by which modafinil increases wakefulness is debated. Herein we used dopamine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(185 citation statements)
references
References 50 publications
7
174
1
3
Order By: Relevance
“…Recent studies suggest that modafinil is a DAT inhibitor in humans and primates (Madras et al, 2006;Volkow et al, 2009). This is further supported by the findings that mice lacking DAT or DA (D1 and D2) receptors do not respond to the wake-promoting effects of modafinil (Qu et al, 2008;Wisor et al, 2001). In vivo microdialysis studies demonstrated that modafinil increases extracellular DA (Wisor et al, 2001;Ferraro et al, 1997;Murillo-Rodríguez et al, 2007).…”
Section: Modafinilmentioning
confidence: 82%
“…Recent studies suggest that modafinil is a DAT inhibitor in humans and primates (Madras et al, 2006;Volkow et al, 2009). This is further supported by the findings that mice lacking DAT or DA (D1 and D2) receptors do not respond to the wake-promoting effects of modafinil (Qu et al, 2008;Wisor et al, 2001). In vivo microdialysis studies demonstrated that modafinil increases extracellular DA (Wisor et al, 2001;Ferraro et al, 1997;Murillo-Rodríguez et al, 2007).…”
Section: Modafinilmentioning
confidence: 82%
“…EEG and EMG recording were made using SLEEPSIGN (Kissei Comtec, Nagano, Japan) [8]. Following data collection, polygraphic recordings were automatically scored offline using SLEEPSIGN (4-s epochs) to determine periods of wakefulness, rapid eye movement (REM) sleep, and non-REM (NREM) sleep, according to standard criteria [8][9][10]. Finally, the defined sleep/wake stages were visually examined and corrected when necessary.…”
Section: Polysomnographic Recordingsmentioning
confidence: 99%
“…However, evidence in both animals and humans supports a predominantly dopamine-mediated action. [3][4][5] Further, it shares many of the psychiatric complications and abuse potential of other psychostimulants. 1 • psychostimulants are only initiated by palliative-care specialists and for short-term use; the GP would only take over prescribing where longerterm use is envisaged or where it is in the patient's best interest…”
Section: Mode Of Actionmentioning
confidence: 99%